1993
DOI: 10.1002/jsfa.2740630206
|View full text |Cite
|
Sign up to set email alerts
|

Saponins of quinoa (Chenopodium quinoa): Effects of processing on their abundance in quinoa products and their biological effects on intestinal mucosal tissue

Abstract: Quinoa (Chenopodium quinoa) is a valuable source of protein in some parts of South America, and it is likely to be exploited further in both developing and industrialised countries. However, quinoa seeds contain significant levels of saponins which are potential antinutrients. In the present study, the effects of processing on the quantity and composition of saponins in quinoa products were determined, and the biological effects of quinoa grain and cereal products containing high or low levcls of saponins were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 12 publications
0
56
0
2
Order By: Relevance
“…The membranolytic activity of saponins has been appreciated for some time and has been exploited in the assay of such compounds by hemolysis of red blood cells. More recently, it has been demonstrated that saponins can damage intestinal mucosal cells by altering cell membrane permeability and interfering with active transport (Gee et al 1993). Saponin from Platycodon grandiflorum induced apoptosis in HT-29 colon cancer cells (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The membranolytic activity of saponins has been appreciated for some time and has been exploited in the assay of such compounds by hemolysis of red blood cells. More recently, it has been demonstrated that saponins can damage intestinal mucosal cells by altering cell membrane permeability and interfering with active transport (Gee et al 1993). Saponin from Platycodon grandiflorum induced apoptosis in HT-29 colon cancer cells (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…High saponin levels were observed in Telferia ocidentalis, Colocacia argente, Lunea taraxacifolia and Ammmarantus viridis, having saponin in mg/100g dry weight, well above 400. Such high level concentration of saponin may necessitate processing that might reduce level of saponin because of its ant-nutrients and other undesirous features such as increasing the permeability of the small intestine, growth impairment and decreased food conversion [19,20] and effect on fertility [21,22]. Thus, intake of these vegetables without proper processing may lead to saponin toxicity, for instance consumption of 100g of fresh Telferia occidentalis would expose the consumer to about 186mg of saponin.…”
Section: Discussionmentioning
confidence: 99%
“…This was shown to decrease food intake [20,21,28,29] and was given as an additional explanation for the incidence of decreased weight gain. A further rationale for the decreased food intake may be due to changes in the expression of gut hormones upon the consumption of quinoa.…”
Section: Effects On Weight Gainmentioning
confidence: 98%
“…It was postulated that the mechanism through which saponins operate revolves around their ability to interfere with intestinal function [29]. Studies in an Ussing chamber showed that the presence of saponins derived from quinoa resulted in an increased conductance of pig jejunum [19].…”
Section: Effects On Weight Gainmentioning
confidence: 99%